2015
DOI: 10.3389/fnins.2014.00441
|View full text |Cite
|
Sign up to set email alerts
|

Computational deconvolution of genome wide expression data from Parkinson's and Huntington's disease brain tissues using population-specific expression analysis

Abstract: The characterization of molecular changes in diseased tissues gives insight into pathophysiological mechanisms and is important for therapeutic development. Genome-wide gene expression analysis has proven valuable for identifying biological processes in neurodegenerative diseases using post mortem human brain tissue and numerous datasets are publically available. However, many studies utilize heterogeneous tissue samples consisting of multiple cell types, all of which contribute to global gene expression value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…The observed gene expression profiles in bulk brain tissue can be dramatically influenced by differences in cellular composition. Such differences can be a result of variation in gray/white matter ratios introduced during tissue extraction, inter-subject variability or represent disease related alterations [14][15][16]. To study the contribution of various technical and biological sources of variation in our dataset we first estimated marker gene profiles (MGPs) for the major classes of cortical cell types (astrocytes, microglia, oligodendrocytes, and neurons) in our samples by summarizing the expression of the cell type-specific marker genes as previously described [15].…”
Section: Cell Composition Is a Major Confounder Of Gene Expression Inmentioning
confidence: 99%
“…The observed gene expression profiles in bulk brain tissue can be dramatically influenced by differences in cellular composition. Such differences can be a result of variation in gray/white matter ratios introduced during tissue extraction, inter-subject variability or represent disease related alterations [14][15][16]. To study the contribution of various technical and biological sources of variation in our dataset we first estimated marker gene profiles (MGPs) for the major classes of cortical cell types (astrocytes, microglia, oligodendrocytes, and neurons) in our samples by summarizing the expression of the cell type-specific marker genes as previously described [15].…”
Section: Cell Composition Is a Major Confounder Of Gene Expression Inmentioning
confidence: 99%
“…200 A recent computational analysis involving genome wide expression data from Parkinson and Huntington disease brain tissue was entirely consistent with the importance of autophagy in these disease processes. 203 …”
Section: Therapeutic Modulation Of Pqc To Curtail Proteotoxicitymentioning
confidence: 99%
“…This gene has also been shown to be associated with different neurodegenerative disorders including PD [Lencz et al., ; Liu et al., ]. Furthermore, previous studies have shown that expression of NSF is decreased in PD substantia nigra [Simunovic et al., ; Elstner et al., ; Capurro et al., ].These data may indicate that the rs897984 mutant allele influences the risk of PD through reducing the level of miR‐4519 and increasing the expression of NSF gene.…”
Section: Discussionmentioning
confidence: 98%